Collaboration Managemen For University-Industry Projects In Sme's Food Processing Industry - Tan, Jin Teik (Universiti Sains Malaysia, 2017)
There is a growing world-wide trend toward greater collaboration between industry and university. It has been recognized that the collaboration between industry and university can initiate innovation and a driver for economic development. The collaborative projects have become important path for Small Medium Enterprises (SMEs) to develop their business. The SMEs lack the technical know-how whilst the university that has these knowledges lacks the information on the company’s problems. Realizing the importance of bridging these technological knowledge gaps, optimizing and leveraging the expertise available at Institute of Higher Learn (IHL), the Ministry of Education Malaysia (MOE) has initiated the Public-Private Research Network (PPRN) projects. PPRN projects are demanding driven projects which are described by companies and experts from IHL provides state of the art technology to solve the problems. However, there are issues and barriers that inhibit the project to its success. The paper study the current scenario of collaborative projects between universities and industry through PPRN, determine the barriers and issues and develop simple model that represent the important issues in collaborative projects. Case study is used as the methodology in this research. Face-to-face interviews are conducted with the manager of 3 SMEs that involved in PPRN project. All of the SMEs are located in Penang area due to time constraint and transport inconvenience. This paper found that the issues and barriers for collaborative project between industry and university from the perspective of Small Medium Enterprises (SMEs) are partnership, project management, benefit, political issues and technology issue which are conform to the literature review. Among the issues discussed, benefit is the most important issue from the perspective of industry. Since the SMEs is the important element of economy growth of Malaysia, the barriers and issues of the collaborative projects must be overcome and leads to successful collaborative projects. The simple model provides hints to succeed more collaborative projects in future.